Antinociceptive effects of morphine and physostigmine in different inbred strains of mice - (:unkn) unknown (My University, 1996)
Antinociceptive effects of morphine and physostigmine, alone or in combination were investigated in mice of BALB/C, C57BL/6 and CB6F1 strains. Morphine and physostigmine increased pain treshold in BALB/C and CB6F1 mice at a dose of 5 mg/kg and 0.1 mg/kg, respectively, whereas C57BL/6 mice were found to be less responsive to both agents. When a nonanalgesic dose of physostigmine (0.05 mg/kg) was combined with a nonanalgesic dose of morphine (2.5 mg/kg), a significant antinociceptive effect was observed in BALB/C and CB6F1 mice, but not in C57BL/6 strain. These results suggest that there is a significant influence of strain on cholinergic and opioid antinociception, and synergistic interaction between cholinergic and opioidergic systems also occur strain-dependently.
Keywords: Analgesia; BALB/C; C57BL/6; CB6F1; Morphine; Physostigmine; Tail-flick